On the paradoxes of informed consent: strictness with unlikely risks, tolerance with certain harm - Carlo Petrini (Istituto Superiore di Sanità, 2013)
The different approaches of two nations to the issues surrounding informed consent by persons with no or limited capacity of understanding are compared. It is important that efforts to ensure formal compliance with consent procedures should not be allowed to distract attention from the risks of harm to individuals.